Akselerasi Dalam Upaya Transformasi Desa Cahaya Negeri Ke Desa Mandiri - Iwi Masika; Nova Ameliya; Bambang Rusdiyanto; Astri Maisa Putri; Syaisa Kina, Dinda; Noval Juandi; Siti Masruroh; Fifin Dwiani; Iisra Kurnia; Sindi Purnama Putri; Nova, Nova Asvio (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
Community Service in the form of KKN (Kuliahan Kerja Nyata) involves contributing to any sector of society. Mosque-based KKN is a type of community service focused on religious activities. A comprehensive understanding of the cultural character and social conditions of the community where KKN takes place is essential for accelerating the adaptation process and socialization with local culture and social conditions. The method used in this journal is observation, where team members actively participate in the field. Team cohesion and cooperation before implementing the planned program are key to the success and smooth execution of the program.